PENGARUH KOMPENSASI DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA KARYAWAN DAN KINERJA KARYAWAN PADA PT. JAYA ASRI GARMINDO KARANGANYAR - Slamet, Giarti; Fridiana, Ika (Surakarta Management Journal, 2023)
The objectives of this study were: 1) To know and explain the significant effect of compensation on employee job satisfaction, 2) Know and explain the significant effect of compensation on employee performance, 3) Know and explain the significant effect of employee work motivation on employee job satisfaction, 4) Know and explain the significant effect of employee work motivation on employee performance, 5) Know and explain the significant effect of employee satisfaction on employee performance. The sample of this study were 55 respondents. The stratified random sampling technique was used to take the sample. The questionnaire is the main instrument for collecting data, and secondary data is obtained from the QC Department. The analysis model used in this research is path analysis. The results of this study indicate that compensation has a significant effect on employee job satisfaction, compensation has a significant effect on employee performance, work motivation has a significant effect on employee job satisfaction, work motivation has a significant effect on employee performance and the most influential is the compensation variable has a major role in PT Jaya Asri Garmindo Karanganyar to increase employee job satisfaction and high employee performance.